AKSESIBILITAS MASYARAKAT MENUJU PASAR GANTING DI KANAGARIAN KAMBANG TIMUR KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Sari, Nia Komala (STKIP PGRI Sumbar, 2014)
This study focused on the issue of accessibility to the Community Pasar Ganting in Kenagarian Kambang Timur Kecamatan Lengayang Kabupaten Pesisir Selatan. This study aims to reveal and describe: Accessibility to the public pasar Ganting seen from mileage, transportation, and transportation infrastructure. The research is a descriptive qualitative research, in Kenagarian Kambang Timur subdistrict Lengayang district Pesisir Selatan. Informants in this study is the sub-district head, village trustees, community leaders, and the people who perform the accessibility to pasar Ganting. The method of collecting data through observation, interviews, and documentation. Data analysis techniques with data reduction, data presentation or display of data, decision-making and verification. The validity of the data with the extension of participation, persistence observation, triangulation, and peer examiners through discussion. The results showed that the accessibility of the public in Kenagarian Kambang Timur to pasar Ganting. viewed from the distance of a variety, there is a short distance away there. Sufficient transportation facilities. in Kenagarian Kambang Timur. available some public transport, such as bibs cigak baruak, motorcycles and tricycles. Poor transport infrastructure, state of the road along the East Kambang Kenagarian up to pasar Ganting There are many hollow road, gravel, dust if the day is hot, and muddy when it rains.